Análise acústica aplicada ao estudo de surdinas de violino: fundamentos para um protótipo modular multifuncional - Marcus Vinicius da Silva Evangelista (2023)
This doctoral research aimed at developing a violin mute prototype based on the analysis of objective data related to its physical characteristics, which can be altered, by different assemblies and configurations of use. This development was based on the acoustic analysis of the alterations produced in the instrument's sonority by different mutes. For data collection and analysis, audio recordings were made under controlled execution conditions, using the acoustic – and psychoacoustic – LTAS, SMS, and Loudness descriptors. Fourteen types of original mutes were selected, among the most used by violinists. Prospects were also carried out to isolate the influence of specific physical characteristics of the different devices on the effects generated on the sound of the instruments. All samplings were done on two violins, with distinct musicians. The results are related to the existing bibliography about the acoustics of the violin, especially the bridge, which suffers the direct action of the mutes. The same analysis methodology was applied to the developed mute prototype for a preliminary evaluation of its effects in different configurations of use. It's hoped, therefore, to contribute to the understanding of the operation of mutes and the alterations produced by their use in the violin's sonority, providing subsidies for a more conscious use by the instrumentalists and the expansion of the possibilities of their application in concert music.